Research progress in high-entropy metallic glasses - YUAN Jiachi; JING Zhiyuan; WANG Xiang; ZHANG Zhibin; JIN Guo; LIANG Xiubing (Cailiao gongcheng)
High-entropy metallic glasses， combining structural disorder of traditional amorphous alloys with the chemical disorder of high-entropy alloys， exhibit excellent thermal stability， magnetic properties， corrosion resistance， and biocompatibility， positioning them as a focal point of recent research. The concept and origin of high-entropy metallic glasses are firstly introduced， followed by a summary of their composition system， preparation methods， and various properties. The reasons for the formation of amorphous structure in high-entropy metallic glasses are analysed from the perspectives of material system and preparation methods. The mechanisms having the good mechanical properties， thermal stability， and corrosion resistance of high-entropy metallic glasses are also explained. Finally， high-throughput material design using material calculations is looked forward to， with an emphasis on the exploration of composite properties， coatings， and other new preparation methods. It is also pointed out that solving fundamental theoretical problems is an important prerequisite for promoting the development of these materials.